The Story of Port Said Stadium: Is It the Psychology of Crowd Panic? Or Architecture Design? - El-Gammal, Yasser O.; Abdel-Razek, Nourhan M. (Journal of Neonatal Surgery, 2025)
Football "Hooliganism" remains a significant issue. Historically, Egyptian football riots have not caused fatalities until the “Port Said” match, which, compounded by the political climate, led to unrest in Cairo, Alexandria, and Suez for 13 days. The media largely attributed the tragedy to “Human Error,” neglecting potential architectural flaws contributing to the disaster. This research paper investigates the Port Said Stadium incident from psychological and architectural perspectives. It aims to ascertain if the tragedy stemmed from panic among spectators, structural deficiencies, or both. The study begins with a literature review of stadium disasters from 1964 to 2010, followed by an analysis of historically "Deadly stadiums," highlighting their vulnerabilities and crowd-related issues. The paper outlines the circumstances surrounding the “Port Said” catastrophe, including Egypt's political environment, audience reactions, legal repercussions, and media portrayal. The methodology consists of two phases: the first explores crowd panic psychology, focusing on panic behavior, fear contagion, social identity, and trust in authorities during crises. The second phase examines the stadium’s architectural design, assessing how these factors exacerbated the disaster's impact. The discussion highlights challenges in gathering reliable data about the stadium and the established assessment criteria that can guide architects in designing safer football venues. Additionally, it presents an architectural redesign proposal for the stadium, incorporating lessons from the tragedy, and suggests recommendations for enhancing audience safety, emphasizing panic mitigation and crowd behavior management during emergencies. Finally, the recommendations outline a comprehensive safety management framework aligned with FIFA guidelines and international standards, emphasizing proactive crowd management, structural resilience, and integrating psychological insights into stadium safety planning..